Analysis of heart rate and scores in student archery athletes - Oktafiranda, N. D.; Ihsani, S. I.; Kuswahyudi, K. (Jurnal Maenpo: Jurnal Pendidikan Jasmani Kesehatan Dan Rekreasi, 2023)
This research aims to determine the heart rate when aiming at DKI Jakarta student archery athletes which will be carried out in May 2023. The research method used is the cross-sectional survey design method. This research instrument is a polar type H10 as a heart rate monitor used by the samples during the archery process. This research was conducted in the Pulomas field, East Jakarta. Sample selection used purposive sampling technique. The sample in this study were DKI Jakarta student athletes who met the criteria, namely 10 recurve athletes. The stages carried out in the data collection process were, heart rate during aiming was measured when the athlete was in the aiming position until release during the archery process using three arrows with a time of 180 seconds per series and carried out in 5 series with a total of 15 arrows. The results of the study showed that male archers had a lower heart rate with an average of 128.13 bpm, while female athletes had an average of 142.37 bpm. The scores for male athletes were higher with an average of 7.97 compared to female athletes with an average score of 6.47. Based on the results of the independent sample test, it is known that the sig. on the heart rate variable 0.026<0.05. Meanwhile, the sig value. on the score variable 0.042<0.05. Each has a sig value. < 0.05. Thus, it can be concluded that there are significant differences in the results of measuring heart rate and scores between male and female athletes.